SECONDARY TRAUMATIC STRESS DAN REKONSILIASI TOKOH UTAMA NOVEL MALAM SERIBU JAHANAM KARYA INTAN PARAMADITHA - Sari, Nita Puspita; Kristianti, Yuliana; Mashud, Mashud (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2023)
In addition to threatening global security and social stability, terrorism also has significant psychological and sociological impacts. The psychological impact does not only occur with the victim's family but also with the perpetrator's family. Focusing on the main character, Mutiara, as the family of the terrorist perpetrator, this research aims to reveal the psychological and sociological impacts as well as Mutiara's reconciliation efforts to survive amidst the bondage of sin and her accountability to society. This research is a descriptive qualitative research. This research will focus on the main character, Mutiara. The approaches used are characterization from M.H Abrams, the concept of Secondary Traumatic Stress (STS) from Charles R. Figley, and the idea of acting out and working through Dominick LaCapra. The results of this study found that the traumatized character experienced secondary trauma which resulted in psychological disorders and severe depression. The main character experiences acting out and working through his life process. The action of working through is used as a strategy to reconcile the trauma she experienced. Pearl's experience in the family of a terrorist is a "middle voice" of "the other’s story" of the terrorism case. However, in MSJ, there is an imbalance in the presentation of the narrative for the victim's family. Instead of providing a space for balance, the novel is too didactic and romanticizes the emotional conflict of the families of terrorists.